Efficient In Vivo Doxycycline and Cre Recombinase–Mediated Inducible Transgene Activation in the Murine Trabecular Meshwork - Liu, Pu (Association for Research in Vision and Ophthalmology, Inc., 2011)
PURPOSE. To generate new mouse lines that facilitate inducible gene activation in the murine trabecular meshwork in vivo. METHODS. Two expression cassettes were knocked into the 3′-UTR of the Myocilin (Myoc) locus, an abundantly expressed extracellular matrix protein produced by cells of the trabecular meshwork. The first cassette directs expression of an inducible form of Cre recombinase, CreER(T2), which is activated by tamoxifen administration under the control of endogenous Myoc regulatory elements. The second cassette contains a reverse tetracycline transactivator, rtTA(M2), which directs the expression of tetracycline-operator transgenes on exposure of animals to doxycycline (Dox). These lines were crossed to GFP and lacZ reporter mice to assay for tamoxifen or Dox-induced transgene expression. RESULTS. Both the Myoc-CreER(T2) and the Myoc-rtTA(M2) lines were capable of directing efficient and inducible expression of transgenes in the murine trabecular meshwork in vivo. In addition, activation of transgenes by Myoc-rtTA(M2) was reversible with loss of transgene expression after Dox withdrawal. Examination of multiple tissues demonstrates efficient transgene activation in the trabecular meshwork, with additional sites of transgene activation including cells in the retina, sclera, lung, kidney, and abundant activation in the neocortex and hippocampus. CONCLUSIONS. Two new mouse lines have been generated that allow for efficient and inducible transgene activation in the murine trabecular meshwork in vivo.